The Role of Modern Internal Audit Activities in Mitigating the Risks of Electronic Services in the Era of Digital Transformation in Banks A Field Study on a Sample of Sudanese Banks. (Sebha University Conference Proceedings, 2024)
The aim of the study was to investigate the role of modern internal audit activities in its dimensions (risk management, governance role, value addition) in mitigating the risks of electronic services in the era of digital transformation in banks. The descriptive analytical method was employed, and a purposive sample was selected from internal auditors and technology management employees in Sudanese banks, including Khartoum, Faisal Islamic, and Omdurman National banks, with a sample size of 65 respondents. A questionnaire was utilized as the data collection tool and SPSS was also used for data analysis. The study concluded that there is a significant interest in mitigating the risks of electronic services in Sudanese banks amidst digital transformation. Moreover, there is a statistically significant impact of modern internal audit activities on mitigating the risks of electronic services in Sudanese banks during digital transformation. The study recommended focusing on enhancing access to electronic services in banks, reinforcing the application of advanced security technologies to protect customer data, empowering customers to regularly monitor their accounts to achieve maximum confidence in digital services, and increasing the emphasis on enhancing and developing modern internal audit activities in Sudanese banks, as these activities play a crucial role in reducing risks associated with electronic services in the digital transformation era.